PENGARUH PERTUMBUHAN EKONOMI, KEMISKINAN DAN KEPADATAN PENDUDUK TERHADAP KRIMINALITAS DI INDONESIA - silvia Silvia; Ikhsan Ikhsan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2021)
Abstract This purpose of examine how much the influence economic growth, poverty and population density in Indonesia. This study uses a panel of data from 33 provinces in Indonesia from 2010-2019. The type of research used in descriptive quantitative using the pooled data method. Choosing a fixed effect model in the analysis, it was found that economic growth has a positive and significant effect, has a positive and significant effect on crime in Indonesia, population density has a significant and significant effect on crime in Indonesia. Therefore, it is hoped that the government will promote stable economic growth, government programs must be pro-poor (pro-poor) with a budget allocation, as well as an even distribution of population and infrastructure. Keywords: Crime, Economic Growth, Poverty, Population Density